Brewing and Serving Alcoholic Beverages to Erlitou Elites of Prehistoric China: Residue Analysis of Ceramic Vessels - He, Yahui; Zhao, Haitao; Liu, Li; Xu, Hong (Frontiers in Ecology and Evolution, 2022)
The Bronze Age in China is characterized by the appearance of bronze ritual vessels, such as gui and he pitchers and jue cups, which were symbols of high social status and likely used in ritual feasting events. Their forms imitate similar ceramic vessels made of white clay. This transformation of such ceramic vessels into their bronze counterparts took place at the Erlitou site in the Yiluo basin, North China (ca. 1800-1500 BC). Such white pottery types are commonly regarded as alcohol-related vessels, but there is a lack of scientific analysis of organic remains on vessels' interior surfaces to understand their functions. In this study, we analyzed microfossil remains on 16 ceramic vessels unearthed from Erlitou and discovered direct evidence of the production and consumption of fermented beverages that were prepared using qu starter as a saccharification agent. Dakouzun wide-orifice vats may have been used for fermentation, likely in semi-solid-state fermentation conditions; narrow-orifice jars zun for storage; gui and he pitchers for heating and/or pouring the beverages; and jue cups for drinking. Monascus mold and herbs were probably used to make qu starter. Fermentation ingredients were primarily rice and wheat, sometimes mixed with broomcorn millet, Job’s tears, roots of snake gourd, among other plants. Rice and wheat were minor crops in the region, probably cultivated for special uses and received by the Erlitou elites as tributary items for making alcoholic beverages. This research demonstrates that Erlitou feasting activities involved serving luxury drinks with prestige utensils in socially exclusive spaces, which emphasized social status, wealth, and power. The development of such drinking materiality and social values coincided with increased social differentiation at the time of early state formation.